(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to find out the anthropometric measurements of the football players. And knowledge of the measurements of special physical qualities and skill scoring by football players category Cubs. And to identify the relation of anthropometric measurements to some physical characteristics and scoring skill of football players. The researcher used descriptive descriptive method on the players of the football team in the category of the 22 cadres. Physical measurements, physical tests and scoring skills were taken for the sample of the research and then were processed statistically. The following main conclusions were reached: Physical and some physical qualities. There was also a significant correlation between physical measurements and football scoring skills. The most important recommendations are: the need to take physical measurements at each stage of life for players to know the rates of physical growth and the extent of their impact in the exercise practice. And the need to choose players with physical specifications standard for the type of game in order to avoid wasting time, effort and money